IPSAS in the Municipal Sector of Iraq and its Importance of Optimal Use of General Funds in Provision of Services - Hatef Sharba, Ali; Abdalkareem Al Baldawi, Shaker (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This document aims to clarify the concept of International Public Sector Accounting Standards (IPSAS), the scope of its application, the steps of its issuance, the interview with IAS and IFRS, and the importance of its adoption through the analysis of the latest international studies for the adoption of IPSAS and plans for future reform complying with these standards. The research took a deductive and analytical approach. The conclusions were the following: there is a global trend towards IPSAS. The number of countries that will adopt IPSAS in 2023 will be 107, which represents 72% of the proportion of successful experiences.